Investigating the Role of Social Responsibility, Organizational Transparency, and Organizational Commitment in Social Cynicism among Secondary School Teachers in Urmia - Rahimi , Robabeh; Vahdat, Roghayeh; Sameri , Maryam (Assessment and Practice in Educational Sciences, 2025)
This study aimed to investigate the predictive role of social responsibility, organizational transparency, and organizational commitment in explaining social cynicism among secondary school teachers in Urmia. The research followed a descriptive-correlational design with an applied developmental objective. The statistical population included all secondary school teachers in Urmia during the 2021–2022 academic year (N = 2670). Using Cochran's formula, a sample of 400 teachers was selected through stratified random sampling. Data were collected using four standardized questionnaires: the Social Cynicism Questionnaire (Afshani & Kebriayi, 2020), the Social Responsibility Questionnaire (Carroll, 1991), the Organizational Transparency Questionnaire (Rawlins, 2008), and the Organizational Commitment Questionnaire (Allen & Meyer, 1990). The internal consistency of the tools was confirmed by Cronbach's alpha coefficients ranging from 0.802 to 0.814. Data analysis was conducted using SPSS, applying Pearson correlation and multiple regression techniques. The results showed that all three independent variables—social responsibility, organizational transparency, and organizational commitment—had significant negative correlations with social cynicism (p ≤ 0.01). The multiple regression analysis revealed that these variables collectively explained 62.2% of the variance in social cynicism (R² = 0.622, p < 0.001), with organizational transparency being the strongest predictor (β = -0.489), followed by social responsibility (β = -0.268) and organizational commitment (β = -0.121). The findings underscore the critical role of ethical and organizational constructs in reducing social cynicism among teachers. By fostering socially responsible behavior, increasing transparency, and strengthening organizational commitment, educational institutions can significantly diminish negative attitudes and promote a more trusting and constructive work environment for educators.